Monitoring heart rate variability and perceived well-being in brazilian elite beach volleyball players: a single-tournament pilot study - Nakamura, F. Y.; Torres, V. B. C.; da Silva, L. S.; Gantois, P.; Andrade, A. D.; Ribeiro, A. L. B.; Brasileiro-Santos, M. d. S.; Batista, G. R. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to monitor the changes in heart rate variability (HRV) and perceptual well-being status after a beach volleyball (BV) tournament day in high-level U17 and senior players. Seventeen BV players (U17 [15-16 years]: n = 08; and senior [19-41 years]: n = 09) competing at national and/or international BV level participated in this study. Resting HRV and perceptual well-being measures were recorded across 4 moments: night 1 (prematches night), morning 1 (prematches morning), night 2 (postmatches night), and morning 2 (postmatches morning). Session rating of perceived exertion was assessed 10 minutes after each match, and accumulated match loads were used for analysis. Senior players presented higher values of natural logarithm of square root of the mean squared differences of successive RR intervals (lnRMSSD) at the 4 observation moments than U17 players (p = 0.006). Within-subjects analysis showed a larger mean difference regarding both lnRMSSD and natural logarithm SD of normal R-R intervals (lnSDNN) between night 1 vs. night 2 in U17 players (effect size = 1.11 and, 0.96, respectively) compared with senior (effect size = 0.40 and 0.32, respectively). Accumulated match loads were negatively correlated with percentage change in lnRMSSD (r = -0.54; p = 0.037). U17 players showed higher well-being variation than senior (group × time; p = 0.02). In conclusion, the lnRMSSD index was able to discriminate the U17 and senior BV players, and maintaining high vagally related HRV indices is an important response to BV training and competition.